2019
DOI: 10.20517/2394-5079.2018.65
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) occurs mostly in individuals with cirrhosis, which is why the guidelines of the most important scientific societies indicate that these patients are included in surveillance programs through the repetition of an ultrasound examination every 6 months. The aim is to achieve early identification of the neoplasia in order to increase the possibility of curative therapies (liver transplantation, surgery or local ablative therapies) and to increase patient survival. HCC nodules arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In particular, the value of a in [1,2], the value of b in [1, 1.2] and the value of g in [1.5, 2] of each case. We used the mean value of the image as the threshold value for applying these a, b, and g values corresponding with specialized cases.…”
Section: Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the value of a in [1,2], the value of b in [1, 1.2] and the value of g in [1.5, 2] of each case. We used the mean value of the image as the threshold value for applying these a, b, and g values corresponding with specialized cases.…”
Section: Preprocessingmentioning
confidence: 99%
“…Currently, indistinct nodular HCCs are the smallest type of HCC that can be clinically detected. The goals of evaluating a hepatic nodule on CT images in a patient with liver cirrhosis include not only identifying the nature of the lesion but also estimating the hepatic extension of the neoplasia and any possible localization in extrahepatic sites (2). From there, a clinician can propose a suitable treatment based on the exact staging of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In cirrhotic patients, its sensitivity is 33%-86%. 12 This wide variation is related mainly to the image quality and experience of the operator, patient-related factors such as body habitus and cooperativeness, and tumor-related factors including tumor size, internal tumor echo-intensity pattern, and tumor location in the liver with diffuse fibro-cirrhotic. 13 Contrast-enhanced ultrasound (CUS) was introduced in the early 2000s to characterize nodules arising in cirrhotic livers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of HCC detection with conventional B‐mode US varies widely. In cirrhotic patients, its sensitivity is 33%–86% 12 . This wide variation is related mainly to the image quality and experience of the operator, patient‐related factors such as body habitus and cooperativeness, and tumor‐related factors including tumor size, internal tumor echo‐intensity pattern, and tumor location in the liver with diffuse fibro‐cirrhotic 13 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] US screening for HCC has a sensitivity of 33%-96% and specificity of 90%-97%, depending on HBV prevalence and various factors such as operator experience, patient habitus, and US technology. 7,8 However, the main challenge to detect early HCC size <2 cm which appearance of small HCC may mimic common other benign lesions such as hemangioma, nodule-like focal fat sparing, focal nodular hyperplasia. 9,10 Current studies reveal that the ultrasound images found in HCC do not have specific characteristics [11][12][13] and are commonly overlapped with other benign lesions.…”
mentioning
confidence: 99%